STRATEGI KOMUNIKASI INTERKULTURAL MAHASISWA ASING DAN LOKAL DI UIN K.H. ABDURRAHMAN WAHID PEKALONGAN : INTERCULTURAL COMMUNICATION STRATEGIES OF INTERNATIONAL AND LOCAL STUDENTS AT UIN K.H. ABDURRAHMAN WAHID PEKALONGAN - Yuliyanti, Tsalisa; Diva Alisaida (LP3M IAI Al-Qolam, 2025)
Communication strategy combines communication planning and management to achieve communication goals. This study focuses on the barriers and intercultural communication strategies between international and local students at UIN K.H. Abdurrahman Wahid Pekalongan, providing insight into interaction dynamics within an Islamic educational environment in Indonesia, which remains underexplored. This research is qualitative with a phenomenological approach. The subjects include nine international students from Thailand, the Philippines, and Malaysia, along with local students who actively interact with them. Primary data were obtained through interviews, observation, and documentation, while secondary data came from official documents and personal archives. Data collection involved observing interactions, interviewing subjects regarding communication barriers and strategies, and supporting documentation. Data analysis utilized an interactive method, including data reduction, presentation, and continuous conclusion-drawing. Findings indicate that international students face communication barriers in Indonesia but adapt to the campus environment by engaging in both passive and active accommodations with local students. There is convergence accommodation as a strategy in which individuals adapt to each other's communicative behaviour, emphasizing language integration, active participation, and respect for social norms. Additionally, divergence accommodation is used to highlight individual differences, both verbally and nonverbally. Here, international students consistently value differences, exhibit flexibility, and learn from experience.